2018
DOI: 10.1002/cpp.2182
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychosocial factors in veteran adjustment to civilian life

Abstract: Our findings suggest that early assessment of experiential avoidance and cognitive reappraisal and the provision of relevant emotion regulation skills training could potentially reduce the veteran's need for more complex (and costly) psychological interventions in the future. Implications for veterans, as well as the services and professionals involved with veteran transition and health care are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…It is not surprising, that while international literature estimates 60-75% of transitioned military members report an easy adjustment to civilian life, others, especially those who developed mental health symptoms or disorders before being discharged, may struggle during this transition period (Bowes et al, 2018;Thompson et al, 2011). Much of the international research on ex-serving military members has consistently highlighted higher rates of disorder and poorer mental and physical health and wellbeing outcomes among those who have transitioned (compared to those who remain in service) (Hatch et al, 2013;Jones et al, 2013;Pinder et al, 2012;Villatte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising, that while international literature estimates 60-75% of transitioned military members report an easy adjustment to civilian life, others, especially those who developed mental health symptoms or disorders before being discharged, may struggle during this transition period (Bowes et al, 2018;Thompson et al, 2011). Much of the international research on ex-serving military members has consistently highlighted higher rates of disorder and poorer mental and physical health and wellbeing outcomes among those who have transitioned (compared to those who remain in service) (Hatch et al, 2013;Jones et al, 2013;Pinder et al, 2012;Villatte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Transition to civilian life for military members has been demonstrated to be a vulnerable period associated with mental health problems and suicide risk 8,9 due to several factors including financial stress, identity issues, psychosocial stress, and coping with physical health problems. [10][11][12] Both CAF and Veterans Affairs Canada (VAC) have commissioned mental health and well-being surveys of military personnel and veterans. 5,13 In 2002, a nationally representative survey of CAF personnel was conducted to estimate the prevalence of mental health problems among Regular and Reserve Force personnel (N ¼ 8,441).…”
mentioning
confidence: 99%
“… 1 , 3 Transition to civilian life for military members has been demonstrated to be a vulnerable period associated with mental health problems and suicide risk 8 , 9 due to several factors including financial stress, identity issues, psychosocial stress, and coping with physical health problems. 10 12 …”
mentioning
confidence: 99%
“…The importance of resilience as a phenomenon is discussed very extensively. Researchers in recent years have confirmed that resilience can be expressed by multidimensional characteristics that vary depending on internal and external stressors and individual life environments [15][16][17]. Resilience can be expressed as a very multi-faceted construct [18], and can be observed as a characteristic [19], a process [20], or a result [21].…”
Section: Introductionmentioning
confidence: 99%